Stature and Jumping Height Are Required in Female Volleyball, but Motor Coordination Is a Key Factor for Future Elite Success. Issue 6 (June 2015) - Pion, Johan A.; Fransen, Job; Deprez, Dieter N.; Segers, Veerle I.; Vaeyens, Roel; Philippaerts, Renaat M.; Lenoir, Matthieu
Abstract : Abstract: Pion, JA, Fransen, J, Deprez, DN, Segers, VI, Vaeyens, R, Philippaerts, RM, and Lenoir, M. Stature and jumping height are required in female volleyball, but motor coordination is a key factor for future elite success. J Strength Cond Res 29(6): 1480–1485, 2015—It was hypothesized that differences in anthropometry, physical performance, and motor coordination would be found between Belgian elite and sub-elite level female volleyball players using a retrospective analysis of test results gathered over a 5-year period. The test sample in this study consisted of 21 young female volleyball players (15.3 ± 1.5 years) who were selected to train at the Flemish Top Sports Academy for Volleyball in 2008. All players (elite, n = 13; sub-elite, n = 8) were included in the same talent development program, and the elite-level athletes were of a high to very high performance levels according to European competition level in 2013. Five multivariate analyses of variance were used. There was no significant effect of playing level on measures of anthropometry ( F = 0.455, p = 0.718, = 0.07), flexibility ( F = 1.861, p = 0.188, = 0.19), strength ( F = 1.218, p = 0.355, = 0.32); and speed and agility ( F = 1.176, p = 0.350, = 0.18). Multivariate analyses of variance revealed significant multivariate effects between playing levels for motor coordination ( F = 3.470, p = 0.036, = 0.59). A Mann-Whitney U test and a sequential discriminant analysis confirmed these results. Previous research revealed that stature and jump height are prerequisites for talent identification in female volleyball. In addition, the results show that motor coordination is an important factor in determining inclusion into the elite level in female volleyball.